A Design of The Underwater Acoustic Beacon Detection and Location Method. (October 2019) - Qu, Jiasheng; Han, Hui; Yang, Shanshan
Abstract: Aiming at the search of the underwater acoustic beacons used in aircraft or ship parameter recorders, this paper mainly introduces the underwater acoustic beacon detection and location method of the short baseline array system. According to the signal form of underwater acoustic beacon, this paper discusses the basic algorithm and the engineering algorithm applied in this system. In theory, the basic algorithm is a necessary algorithm for short baseline array to calculate target azimuth, which including the two-element linear array direction measurement algorithm, two-direction cross-location algorithm and the virtual direction discrimination algorithm. In addition, according to the experience of offshore operations, this paper introduces the engineering practice methods such as the angle measurement, the data extraction, the location ray screening and the location ray starting point coordinate calculation. The combination of engineering algorithm and basic algorithm can effectively reduce the impact of the test equipment and environment, and improve the accuracy of underwater acoustic beacon detection and position, which has been tested in actual operation at sea.